Antimicrobial stewardship program (ASP): an effective implementing technique for the therapy efficiency of meropenem and vancomycin antibiotics in Iranian pediatric patients - Aliakbar Rahbarimanesh; Sayed Yousef Mojtahedi; Payman Sadeghi; Maryam Ghodsi; Sara Kianfar; Leila Khedmat; Saeedreza Jamali Moghadam Siyahkali; Mohammad Kaji Yazdi; Anahita Izadi (BMC, 2019)
Abstract Background Antimicrobial stewardship program (ASP) is a distinguished method to improve the prescription and efficacy of antibiotics. Aim The efficacy of ASP and conventional methods was compared to measure the effectiveness of meropenem (MPM) and vancomycin (VMN) antibiotics in pediatric patients. Design In an interventional quasi-experimental study, 135 children admitted in Children's Hospital affiliated to University of Medical Sciences in time periods of 2014-2015 and 2015-2016 were assessed. Methods The conventional and ASP methods in 2014-2015 and 2015-2016 were respectively utilized to provide the best antimicrobial therapy of MPM and VMN antibiotics in patient children. The data of mortality rate (MR), antibiotic prescription (AP), antibiotic dose (ADe), antibiotic duration (ADn), length of hospital stay (LOHS), and blood cultures (BCs) were compared across the years using the Chi square, independent t test, and Fisher's exact test. Results The levels of MR, AP, ADe, ADn, LOHS, and positive BCs using the ASP method in 2015-2016 were significantly lower those of in 2014-2015 using the conventional one (p < 0.05). Conclusions The ASP method versus conventional one with a better efficacy can be employed as an antibiotic administration guide for MPM and VMN in the therapy of patients in community-based hospitals.